Human resource needs and costs for HIV pre-exposure prophylaxis provision in nurse-led primary care in Eswatini and opportunities for task sharing - Kohler, Stefan; Dalal, Shona; Hettema, Anita; Matse, Sindy; Bärnighausen, Till; Paul, Nicolas (Human resources for health, 2022)
The global expansion of HIV pre-exposure prophylaxis (PrEP) includes health systems that face a shortage of skilled health care workers (HCWs). We estimated the human resource needs and costs for providing PrEP in nurse-led primary care clinics in Eswatini. Furthermore, we assessed potential cost savings from task sharing between nurses and other HCW cadres.
Gesehen am 10.01.2023